AN ANALYSIS OF THE ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 38 PEKANBARU IN COMPREHENDING DESCRIPTIVE TEXTS - Rahayu Ika Putri; Syofia Delfi; Mahdum ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was designed to describe the student’s ability in comprehending descriptive texts and aimed to find out the students ability in comprehending descriptive texts for each component and the level of Bloom’s Taxonomy Revised indicated in the ability. This research was conducted at SMPN 38 Pekanbaru that collected April to May 2017. The try out class was VIII-3 (30 students) and the sample was VIII-1 (30 students) chosen by cluster random sampling. The result showed that the ability of the second year students of SMPN 38 Pekanbaru in comprehending descriptive texts for each component is in good level which the mean score was 61.7, however, the students have not passed the minimum score of the school which is 75. For the level of remembering; finding factual information the mean score was 78, finding meaning of difficult words was 40.7. The level of understanding (finding references) the mean score was 76. For the analyzing level; finding main idea the mean score was 55.3, finding restatement was 50, and the level of evaluating (finding social function) was 70. Therefore, this research suggested the English teachers to focus on the level and components that students still find difficulities and categorized them into poor level. Students should learn the components in descriptive texts and other text types. Further researchers are expected to find the standard guidance of classification of Bloom’s Taxonomy Revised indicated the components of reading comprehension.Key Words: Student’s Ability, Bloom’s Taxonomy Revised, Comprehending Descriptive Texts.